TECHNICAL AND ECONOMIC STUDY ON LANDMARKS FROM A.D.I. - Ioan Milosan (European Scientific Journal, ESJ, 2015)
The paper presents an experimantal study regarding the obtaining of 3 landmarks for the automotive industry, made from 4 alloyed Austempered Ductile Irons (A.D.I.) and made a technical and economic study aiming to achieve maximum benefit, from using the 3 landmarks. For this process were used in the following specifications: A.D.I. materials, the specific amount of materials (T1-T4) treated daily for achieving the landmarks (L1, L2, L3), quantity available of A.D.I. materials, using the calculation of Simplex algorithm - the One Phases’ Method.